Postoperative single versus multiple fractions high-dose rate iridium-192 surface mould brachytherapy for keloid treatment: a comparative study. Issue 1 (20th June 2017) - Ahmad, Misbah; Ahmad, Habib; Khattak, Muhammad Rauf; Shah, Kamran Ali; Javed, Nabila; Shah, Syed Jawad Ali; Shaheen, Wajeeha; Mansoor, Kehkashan
Abstract: Background and purpose: In developing countries like Pakistan the cost effectiveness and patient convenience in any treatment modality is a question of major concern. The purpose of this study was two-fold; first to report our experience with a high-dose rate Iridium-192 surface mould brachytherapy of keloid scars after surgical excision, using different radiation treatment regimen and second to establish the most convenient and cost effective treatment protocol having no compromise on the treatment outcomes. Materials and methods: From January 2012 to April 2015 a total 51 patients with 65 keloid lesions underwent postoperative Iridium-192 high-dose rate surface mould brachytherapy. The dose regimen used was: 8 Gy in a single fraction, 10 Gy in a single fraction, 15 Gy in three fractions and 18 Gy in three fractions. The median follow-up period was 33 months (range 15–53 months). Results: The success rates were 57·2, 89·5, 85 and 89·5% for the treatment regimen of 8 Gy/F×1, 10 Gy/F×1, 5 Gy/F×3 and 6 Gy/F×3, respectively. Grade 2 or above radiation induced toxicity was not observed. Findings: The results of this study show that a dose regimen of 10 Gy (biological effective dose=20 Gy) in a single fraction have comparable results with a dose regimen of 15 Gy in three fractions or 18 Gy in three fractions. 10 Gy in a single fraction is therefore the most convenient and cost effective dose regimen for the management of keloid scars in developing countries like Pakistan, while 8 Gy in a single fraction is considered suboptimal and discouraged in practice.